Evaluating solar photovoltaic panel orientations for an open-field internet of things framework - Khairul Anuar Mohamad; Mohamad Syahmi Nordin; Hairul Hafizi Hasnan; Ahmad Fateh Mohamad Nor; Rohaiza Hamdan; Nazirah Mohamad Abdullah; Nor Anija Jalaludin (Institute of Advanced Engineering and Science, 2026)
This paper presents a comparative experimental analysis of horizontal, vertical, and 45° tilt photovoltaic (PV) panel orientations, evaluated with and without load conditions in a tropical environment. Simultaneous measurements of open-circuit voltage (Voc), short-circuit current (Isc), and average power were conducted over three consecutive days to facilitate orientation-specific performance comparisons. Results show that the horizontal orientation demonstrated robust midday performance, achieving 3.65 W with load on one of the test day, but declined sharply in post-noon periods. The vertical orientation consistently produced lower average power outputs, approximately 3.1 W with load. As a reference, the 45° tilt consistently produced the highest output, with average load powers of 3.77 W, 3.41 W, and 3.64 W over the three days. This performance exceeded horizontal orientations by 2–5% and vertical orientations by 15–20%. Both horizontal and tilt orientations consistently surpassed internet of things (IoT) operational thresholds of 3.3–5.0 V and 100–200 mA required for low power sensor nodes, ensuring excess energy for storage. In contrast, the vertical orientation posed a risk of inadequate current in late afternoon periods. Thus, the results indicate that the orientation selection should be environment-driven. Horizontal or tilted orientations are suitable for rural and open-field IoT settings, while vertical orientations are advantageous for space-constrained or dust-prone environments.